Thalidomide-Revisited: Are COVID-19 Patients Going to Be the Latest Victims of Yet Another Theoretical Drug-Repurposing? - Khalil, Athar; Kamar, Amina; Nemer, Georges (Frontiers in Immunology, 2020)
The coronavirus disease 2019 (COVID-19) pandemic is a worldwide threatening health issue. The progression of this viral infection occurs in the airways of the lungs with an exaggerated inflammatory response referred to as the “cytokine storm” that can lead to lethal lung injuries. In the absence of an effective anti-viral molecule and until the formulation of a successful vaccine, anti-inflammatory drugs might offer a complementary tool for controlling the associated complications of COVID-19 and thus decreasing the subsequent fatalities. Drug repurposing for several molecules has emerged as a rapid temporary solution for COVID-19. Among these drugs is Thalidomide; a historically emblematic controversial molecule that harbors an FDA approval for treating erythema nodosum leprosum (ENL) and multiple myeloma (MM). Based on just one-case report that presented positive outcomes in a patient treated amongst others with Thalidomide, two clinical trials on the efficacy and safety of Thalidomide in treating severe respiratory complications in COVID-19 patients were registered. Yet, the absence of substantial evidence on Thalidomide usage in that context along with the discontinued studies on the efficiency of this drug in similar pulmonary diseases, might cause a significant obstacle for carrying out further clinical evaluations. Herein, we will discuss the theoretical effectiveness of Thalidomide in attenuating inflammatory complications that are encountered in COVID-19 patients while pinpointing the lack of the needed evidences to move forward with this drug.